Teachers’ Obstacles of Online Learning Process During Pandemic Era (A Study of English Teachers at Golden Kidz School, West Jakarta) - Nurul Isrofiah; Hermariyanti Kusumadewi (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
The objective in this research is that there are various obstacles in the implementation of online learning due to the impact of the COVID-19 pandemic experienced by Golden Kidz teachers, Jakarta. This research uses a descriptive case study design with a qualitative approach. In this research, the key instrument is the researcher. The data in this study are the obstacles faced and the source of interview data from subject teachers at the Golden Kidz School Jakarta, there are 3 people. They were selected as informants based on the problems experienced by the teacher during the implementation of online learning. Collecting data using interview techniques. To test the validity of the data, the researcher triangulated the time by comparing the results of the interviews. Based on data analysis, the results of the study indicate that there are several obstacles that become teacher problems during online learning at Golden Kidz School. These problems include (a) internet access, (b) technology literate, (c) lack of student interest in learning, (d) difficult communication, (e) limitation of teachers in preparing learning materials.